Bhuwan Lal Joshi y Leo E. Rose, Democratic innovations in Nepal. A case study of political acculturation. University of California Press, Berkeley, 1966. XVI, 551 pp. - Fürer-Haimendorf, Christoph von (El Colegio de México, 1967)
-